Protective Effects and Mechanisms of Selenium Enriched Sweet Potato Starch Noodles on Liver Injury in D-Galactose-induced Aging Mice - Mengjia ZHU; Yuling ZHANG; Chunhao GAO; Tao LI; Wei LI; Xiang GAO (Shipin gongye ke-ji)
In the present study, the protective effects and mechanisms of selenium enriched sweet potato starch noodles on oxidative injury of liver in D-galactose-induced aging mice were investigated. An oxidative damage model in mice was established through intraperitoneal injection of D-galactose (D-Gal). The intervention groups received diets supplemented with Cardamine violifolia, selenium protein, and selenium-enriched sweet potato starch noodles at a selenium dose of 10 μg/kg·d−1. A normal starch noodles control group was enrolled. The intervention lasted 28 consecutive days. The results showed that there was no difference in growth parameters among all groups. Compared with normal group, the liver structure of model group was significantly damaged, serum ALT and AST were increased (P<0.01), liver oxidative stress was aggravated (SOD, GSH-Px, T-AOC, HO-1 were decreased, MDA was increased, P<0.01), and hepatic levels of inflammatory cytokines TNF-α and IL-6 were increased (P<0.01). Compared with model group, Cardamine violifolia, selenium protein, and selenium-enriched sweet potato starch noodles significantly improved liver morphology, decreased serum ALT and AST levels (P<0.01), increased liver SOD and HO-1 levels (P<0.05), and decreased liver IL-6 and TNF-α concentration (P<0.01). Both selenium-enriched raw material and selenium-enriched starch noodles could significantly down-regulate the relative expression of Keap1 and up-regulate that of Nrf2 in liver of D-Gal treated mice (P<0.01). Selenium-enriched starch noodles also markedly increased the relative abundance of beneficial gut microbiota, such as Verrucomicrobiota, Akkermansia, Bacteroides, Lachnoclostridium and Blautia (P<0.05), and promoted the secretion of fecal levels of short-chain fatty acids (SCFAs). The intestinal bacteria and SCFAs regulated by selenium-enriched starch noodles were related to the protection against liver injury. In summary, Cardamine violifolia, selenium protein and selenium-enriched sweet potato starch noodles improved D-Gal induced liver injury, and the mechanism was related to the activation of Keap1-Nrf2/HO-1 signaling pathway and improvement of intestinal microbial composition. The results provide a theoretical basis for the nutritional enhancement of starch noodles and the development of selenium-rich starch noodles.